Risk Analysis of Money Laundering through Special Purpose Vehicle (SPV) in International Business - Judijanto, Loso; Soraya, Qubaila Fazrin Ega; Sudiana, Urip; Sutanto, Himawan (West Science Business and Management, 2024)
The misuse of Special Purpose Vehicles (SPVs) in international business has emerged as a significant risk in global money laundering schemes. This study explores the mechanisms, risk factors, and regulatory challenges associated with SPVs, emphasizing their dual role as legitimate financial instruments and potential tools for illicit financial activities. A comprehensive literature review highlights key vulnerabilities, including opaque ownership structures, jurisdictional arbitrage, and regulatory inconsistencies. The findings underscore the necessity of enhanced transparency, international collaboration, and technological adoption to mitigate these risks. Proposed strategies include mandating beneficial ownership disclosure, leveraging blockchain and artificial intelligence for transaction monitoring, and strengthening global anti-money laundering (AML) frameworks. By addressing these challenges, this study contributes to safeguarding the integrity of financial systems and promoting ethical practices in international business.